2014
DOI: 10.1377/hlthaff.2013.1087
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence On The Affordable Care Act: Coverage Impacts Of Early Medicaid Expansions

Abstract: The Affordable Care Act expands Medicaid in 2014 to millions of low-income adults in states that choose to participate in the expansion. Since 2010 California, Connecticut, Minnesota, and Washington, D.C., have taken advantage of the law's option to expand coverage earlier to a portion of low-income childless adults. We present new data on these expansions. Using administrative records, we documented that the ramp-up of enrollment was gradual and linear over time in California, Connecticut, and D.C. Enrollment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 16 publications
3
123
1
Order By: Relevance
“…For instance, previous research (Skopec, Musco, and Sommers, 2014) showed that the mean difference in the uninsured rate in the BRFSS and ACS was 3.3 percentage points, similar to the mean absolute differences of 2.8 to 6.2 percentage points for our measures in Appendix eTable 1. That study also found that the concordance for access-to-care measures across government surveys is lower than for coverage measures.…”
Section: Survey Response Ratesupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, previous research (Skopec, Musco, and Sommers, 2014) showed that the mean difference in the uninsured rate in the BRFSS and ACS was 3.3 percentage points, similar to the mean absolute differences of 2.8 to 6.2 percentage points for our measures in Appendix eTable 1. That study also found that the concordance for access-to-care measures across government surveys is lower than for coverage measures.…”
Section: Survey Response Ratesupporting
confidence: 85%
“…1,3,[11][12][13] Beyond coverage and access, research to date has demonstrated limited impact of the Medicaid expansion on utilization, preventive care, and health. However, coverage expansions can take several years to reach full enrollment, 14 so there is a critical need for longerterm studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several states opted to expand Medicaid under the ACA prior to 2014, and studies indicate small marginal changes in coverage with variable crowd-out -little among those with health problems, but significant among younger adults (Sommers, Kenney, & Epstein, 2014). For the 2014 expansion, federal survey data (Cohen & Martinez, 2014;Smith & Medalia, 2015) and private data sources (Shartzer, Long, Karpman, Kenney, & Zuckerman, 2015;Sommers, Gunja, et al, 2015) all confirm a large drop in the uninsured rate, particularly among lower-income adults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the literature on state-level Medicaid expansions prior to the ACA suggests that coverage expansions increase Medicaid enrollment even though take-up of Medicaid coverage among the newly eligible is often low (Long, Zuckerman, and Graves, 2006;Sommers, Baicker, and Epstein, 2012;Sommers, Kenney, and Epstein, 2014). The literature is more mixed regarding the degree to which expansions lead to offsetting decreases in private coverage, a phenomenon known as crowd-out.…”
Section: Related Literaturementioning
confidence: 99%
“…We follow Sommers, Kenney, and Epstein (2014) in coding Minnesota's income limit as 75 percent of the FPL. 9 • New Jersey: TRIM3 reported 200 percent for parents versus 27 percent (61 percent MAGI) in the MAGI conversion reports.…”
Section: Magi Conversion Plans As Data Source On Medicaid Limitsmentioning
confidence: 99%